Analisis Pendapatan Kelompok Tani Hutan Wana Mitra Lestari Terhadap Kemitraan Kehutanan di Desa Napal Putih: Income Analysis of Wana Mitra Lestari Forest Farmer Group on Forestry Partnership in Napal Putih Village - Sinurat, Marta Maria; Ahyaudin, Ahyaudin; Muryunika, Rince (Fakultas Kehutanan Universitas Jambi, 2023)
ABSTRACT The Wana Mitra Lestari Forest Farmer Group is one of the forest farmer groups located in Napal Putih Village, Serai Serumpun District. The forest work area managed by KTH Wana Mitra Lestari is a production forest area. KTH Wana Mitra Lestari has obtained permission to access management for protection and recognition of Forestry partnerships sourced from the Ministry of Environment and Forestry through a decree No. 10665/Menlhk-PSKL/PSL.0/12/2019. The area of KTH Wana Mitra Lestari is 90 Ha. Land management owned by KTH members is managed individually according to the KTH member's land area. The rubber production of KTH Wana Mitra Lestari is sold to an HTI company in Tebo Regency. This research was conducted in Napal Putih Village, Serai Serumpun District, Tebo Regency. This research aims to analyze the differences in income of KTH Wana Mitra Lestari farmers before and after implementing the forestry partnership. The data collection system was carried out using interviews and with the help of questionnaires and literature studies to support the research results. Sampling was carried out using the saturated sample method (census). The data analysis used in this research is descriptive analysis and quantitative analysis with calculations of income, costs, revenue, R/C-ratio and average difference tests. Based on the results of research conducted, forestry partnerships can become a community empowerment program around forest areas by forming Forest Farmer Groups to increase farmers' income. The calculation results of KTH Wana Mitra Lestari's total income before the forestry partnership were IDR 18,413,181/farmer/year while the income after the forestry partnership was IDR 32,130,748/farmer/year. The results of the R/C Ratio analysis of KTH Wana Mitra obtained an R/C Ratio before the forestry partnership with a value of 5.20, whereas after the forestry partnership it was 5.37, which means that the KTH Wana Mitra Lestari farming business is worth developing because the R/C Ratio is > 1. Results of the analysis of the mean difference test - The average obtained is that there is a difference between the total productivity of KTH Wana Mitra Lestari farmers before and after the forestry partnership with a significant value (2-tailed), namely (0.001 < 0.05) or smaller than alpha 5% so that Ha is accepted and Ho is rejected. Keywords: Income Analysis, Forestry Partnership, R/C-ratio ABSTRAK Kelompok Tani Hutan Wana Mitra Lestari merupakan salah satu kelompok tani hutan yang berada di Desa Napal Putih Kecamatan Serai Serumpun. Areal kerja kawaan hutan yang dikelola KTH Wana Mitra Lestari merupakan kawasan hutan produksi. KTH Wana Mitra Lestari telah memperoleh ijin akses kelola perlindungan dan pengakuan kemitraan Kehutanan yang bersumber dari Kementerian Lingkungan Hidup dan Kehutanan melalui SK. No. 10665/Menlhk-PSKL/PSL.0/12/2019. Luasan areal KTH Wana Mitra Lestari yaitu 90 Ha. Pengelolan lahan yang dimiliki anggota KTH dikelola secara individu sesuai dengan luas lahan anggota KTH. Hasil produksi karet KTH Wana Mitra Lestari dijual kepada salah satu perusahaan HTI di Kabupaten Tebo. Penelitian ini dilakukan di Desa Napal Putih Kecamatan Serai Serumpun Kabupaten Tebo. Penelitian ini bertujuan untuk menganalisis perbedaan pendapatan petani KTH Wana Mitra Lestari sebelum dan setelah penerapan kemitraan kehutanan. Sistem pengumpulan data dilakukan dengan wawancara serta bantuan kuesioner serta studi literatur untuk menunjang hasil penelitian. Penentuan pengambilan sampel dilakukan menggunakan metode sampel jenuh (sensus). Analisis data yang digunakan dalam penelitian ini yaitu analisis deskriptif dan analisis kuantitatif dengan menghitung penerimaan, biaya, pendapatan, R/C-ratio serta uji beda rata-rata. Berdasarkan hasil penelitian yang dilakukan bahwa melalui kemitraan kehutanan dapat menjadi suatu program pemberdayaan masyarakat disekitar kawasan hutan dengan membentuk Kelompok Tani Hutan untuk meningkatkan pendapatan petani. Hasil perhitungan pendapatan total KTH Wana Mitra Lestari sebelum kemitraan kehutanan sebesar Rp.18.413.181/petani/tahun sedangkan pendapatan setelah kemitraan kehutanan sebesar Rp.32.130.748/petani/tahun. Hasil analisis R/C ratio KTH Wana Mitra diperoleh R/C ratio sebelum kemitraan kehutanan dengan nilai 5.20, sedangkan setelah kemitraan kehutanan 5.37 yang artinya usaha tani KTH Wana Mitra Lestari layak dikembangkan karena R/C ratio > 1. Hasil perhitungan uji beda rata-rata diperoleh terdapat perbedaan antara jumlah produktivitas petani KTH Wana Mitra Lestari sebelum dan setelah kemitraan kehutanan dengan nilai signifikan (2-tailed) yaitu (0,001 < 0.05) atau lebih kecil dari alfa 5% sehingga Hâ‚ diterima Ho ditolak. Kata Kunci: Analisis Pendapatan, Kemitraaan Kehutanan, R/C-ratio